Relationship between iron deficiency and severity of tuberculosis: Influence on T cell subsets - Zheyue Wang; Zhenpeng Guo; Qiang Zhang; Chenchen Yang; Xinling Shi; Qin Wen; Yuan Xue; Zhixin Zhang; Jianming Wang (iScience)
Summary: Tuberculosis (TB) remains a leading cause of death globally, with nearly half of TB patients experiencing iron deficiency. The role of iron supplementation as an adjunct therapy remains controversial. This study examines the impact of iron deficiency on TB progression and immune function. We conducted a case-control study involving 808 pulmonary TB patients recruited from Changzhou Third People’s Hospital (2018–2022) to investigate the association between serum iron levels and TB severity. Additionally, we evaluated the relationship between baseline serum iron levels and pulmonary lesion characteristics during antituberculosis treatment using a cohort study of 89 patients. We observed that low serum iron was associated with more severe lung symptoms, decreased MAIT, Vδ2+, and Treg cell percentages, and increased interleukin-1β (IL-1β) and IL-7 levels. Findings suggest that iron deficiency may exacerbate lung lesions by altering T cell subsets and cytokine profiles.